Modified Numerical Modeling of Axially Loaded Concrete-Filled Steel Circular-Tube Columns - Nguyen, P. C.; Pham, D. D.; Tran, T. T.; Nghia-Nguyen, T. (Engineering, Technology & Applied Science Research, 2021)
Predicting the behavior of concrete in a Concrete-Filled Steel Tubular (CFST) column is challenging due to the sensitivity to input parameters such as the size of the cross-section, the material modeling, and the boundary conditions. The present paper proposes a new modified finite element model to predict the behavior and strength of a CFST subjected to axial compression. The development is based on the concrete damaged plasticity model, with its stress-strain relationship revised from the available model. The predicted accuracy of the modified model is verified via a wide range of experimental tests. The proposed model has more accuracy than the available models in predicting the ultimate compression strength. The results show good agreement with the test data, allowing its use in modeling CFST columns.